The 1994 CIA World Factbook - United States. Central Intelligence Agency (Salt Lake City, UT : Project Gutenberg, 1994)
"The 1994 CIA World Factbook" by United States Central Intelligence Agency is a reference resource published in 1994. This almanac-style compendium provides comprehensive summaries of demographics, geography, communications, government, economy, and military information for countries and territories worldwide. Originally created for U.S. government officials, this public domain work draws from numerous federal agencies and departments. It offers readers a systematic snapshot of global political entities, dependencies, and disputed territories, reflecting both statistical data and the geopolitical perspectives of its era. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_World_Factbook
Release date is 1994-11-01
Keywords: World politics -- Handbooks, manuals, etc; Geography -- Handbooks, manuals, etc; Political science -- Handbooks, manuals, etc; Political statistics -- Handbooks, manuals, etc